Sistem Informasi Kesehatan Mata Berbasis Web untuk Memfasilitasi Pemeriksaan Mata pada Siswa Sekolah Dasar - Ramadhan, Muh. Gilang; Rahmah, Riska Sri; Fatimah, Farah Hartiningtias (Journal of Security, Computer, Information, Embedded, Network, and Intelligence System, 2024)
The increased use of gadgets among children has led to a significant rise in cases of myopia among elementary school students. This study aims to design and develop a web-based Eye Health Information System to facilitate eye examinations for elementary school students. The development method used in this study is the waterfall model, which includes the stages of requirement analysis, design, coding, testing, and system implementation. The results of the study show that the developed information system provides essential features such as appointment scheduling with eye doctors, access to educational videos, and online consultations, all designed to raise awareness and improve access to eye health services for students. System testing demonstrates that all features function as expected, with a user-friendly and responsive interface. In conclusion, this system is expected to be an effective tool in supporting eye health examinations and improving the quality of health services for elementary school students.